Phytoremediation of arsenic in constructed wetland using Pennisetum purpureum Schumach. and plant growth-promoting rhizobacteria - Rahman, Md. Ekhlasur (2023)
Nowadays there are many types of technologies to restore contaminated areas with heavy metals. One of the technologies that belong to a green technology is the remediation of soil and groundwater contaminated with heavy metals using plants and plant growth-promoting rhizobacteria (PGPR). This technology is known as PGPRassisted phytoremediation in the world. Among the advantages of phytoremediation are a cost-effective, environmentally friendly and it can be used as an alternative for bioenergy. The research was conducted to search for potential plants which can be used in phytoremediation mainly for inorganic arsenic in arsenate form [As(V)]. The objectives of this study were to determine the maximum concentration of As that could be taken up by Pennisetum purpureum in phytoremediation, to identify the role of rhizobacteria in the root of P. purpureum which can enhance phytoremediation process, to determine the mechanisms of As uptake and bioaccumulation by P. purpureum and to optimize the As phytoremediation process using pilot reed beds. As phytotoxicity test, rhizobacteria isolation, molecular identification of rhizobacteria, qualitative and quantitative screening of the rhizobacterial isolates for As-tolerance, determination of different plant growth-promoting traits, As phytoremediation in pilot reed beds, determination of different enzyme activity in pilot reed beds and the optimization of phytoremediation process were included in this study. Results of rhizobacteria isolation showed that two gram-positive and seven gram-negative rhizobacteria that resistant to As. Almost all rhizobacteria (nine) through molecular identification showed excellent performance on As tolerance and different plant growth-promoting activity. Among them Bacillus australimaris showed the highest performance on As-tolerant and different plant growth-promoting activity. Based on SEM-EDX and TEM-EDX analysis showed that there was a difference between B. australimaris in control and exposed with As. P. purpureum was able to survive up to 40 mg kg-1 As concentration for 77 days of exposure at the time of advanced phytotoxicity test. The amount of bioaccumulation of As in entire P. purpureum on 77 days reached 2,323.22 ± 74.34 mg kg-1 dry weight with bioaccumulation factor 0.23 ± 0.006, translocation factor 0.87 ± 0.028, percentages of translocation 42.92 ± 1.2 and calorie value of P. purpureum 16,841.32 ± 199.10 J g-1. Results on phytoremediation of As in non-aerated pilot reed beds showed that the highest amount of As bioaccumulation by P. purpureum that occurred in the As concentration of 39 mg kg-1 at a retention time of 42 days was 5,733.28 ± 68.80 mg kg-1 dry weight. The addition of aeration in pilot reed beds could enhance toxic effect of As on P. purpureum although the accumulation of As increased. Optimization results on the phytoremediation process with concentration of 39 mg kg-1 As showed that addition of nine rhizobacteria consortium and NPKS fertilizer could alleviate the As toxic effect and increase the biomass of P. purpureum, however the total As bioaccumulation ability increased and its highest uptake was 6,944.48 ± 69.44 mg kg-1 dry weight. Results of SEM-EDX analysis of fresh roots, stems and leaves of P. purpureum revealed significant differences in the context on the effect of As on plant tissue and uptake of As between control and different treatments. In conclusion, P. purpureum is an As hyperaccumulator plant but it is sensitive to high concentration of As and the addition of PGPR consortium has enhanced both the growth of P. purpureum and the As accumulation. These results suggest that PGPR-assisted phytoremediation of As in constructed wetland can be used in As phytoremediation in agricultural polluted areas and anthropogenically polluted environments due to its high capability to uptake and bioaccumulation of As.